(untitled) (World Bulletin of Management and Law, 2023)
This article examines the theoretical and legal aspects of using artificial intelligence technologies in healthcare system. Focusing on key elements such as the current applications of AI in medical practice, its potential prospects and emerging challenges, the application of international standards and legal accountability, the article analyzes various studies demonstrating the diverse uses of AI in healthcare, highlighting both the benefits and challenges associated with its implementation. The article also emphasizes the legal basis for AI decision-making, algorithmic bias, transparency and the need for human oversight.